ANALYSIS OF INTERLEUKIN-6 AND TUMOUR NECROSIS FACTOR-ALPHA EXPRESSION AFTER THERAPY OF ROSELLE FLOWER EXTRACT (HIBISCUS SABDARIFFA L) ON THE INCISION WOUND LIPS WISTAR RAT - Yayun Siti Rochmah; Erwid Fathur Rahman; Jaka Kusnanata; Rama Putranto; Aqiila Hasna Edwina; Anggraenifa Nurul Auliya (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground: The healing of wounds in the lip region is impeded by the fact that chewing food and speaking can exert pressure and attract the wound. Rosella flowers were chosen because they contain anti-inflammatory flavonoids, anthocyanins, tannins, and saponins, as opposed to chemical medications for wound healing that often induces negative effects. Purpose: This study's objective was to assess the influence of 15% roselle flower extract (Hibiscus sabdariffa L) in a paste formulation on the expression of IL-6 and TNF Alpha during the incision wound healing phase. Method: The method is experimental analytic research with post-test-only control group design. There were two groups: control group and the treatment group. Each group contains 3 Rattus Norvegicus. They were incisions in the upper labial mucosa using blade with a length of 5 mm and a depth 1 mm. Roselle flower extract (Hibiscus sabdariffa L) 15% was applied two times per day for three days in treatment group. After the treatment, the rats were sacrificed to check the expression of IL-6 and TNF Alpha using the Immunohistochemistry method. Result: The results of the analysis of the ANOVA-test show that for TNF Alpha expression it has a significant value (p) of 0.054 or p > 0.05, meaning that there is no significant difference. Meanwhile, the IL-6 expression obtained a significant value (p) of 0.009, meaning that there was a significant difference between the control and treatment groups. Conclusion: The study concluded that 15% rosella flower petal extract in a paste reduced IL-6 expression during the inflammatory but not TNF Alpha. Keyword : Roselle flower; Interleukin 6 (IL-6); TNF Alpha, Oral mucosa; Wound healing